Produksi Wacana Dakwah dalam Tafsir Al-Qur’an Berbahasa Jawa: Analisis Power/Knowledge - Anita Sartika; Wahyu Hidayat (CV. Era Digital Nusantara, 2026)
The interpretation of the Qur'an is never born in a neutral space, but always interacts with the social, cultural context, and power relations surrounding its interpreters. This study aims to analyze how Javanese and Muhammadiyah cultures influence the construction of meaning in the Qur'an Jawen and Tafsir Qur'an Jawen Pandum lan Panduming Dumadi. The study uses a qualitative method based on a literature review, using the two commentaries as primary data sources. The analysis is carried out through Michel Foucault's power/knowledge approach to examine the relationship between tafsir and Muhammadiyah's socio-religious authority, as well as Hans-Georg Gadamer's hermeneutics, especially the concept of fusion of horizons, to understand the process of meaning formation in the socio-cultural context of colonial Java. The results of the study show that the use of Javanese with the Carakan script not only functions as a medium of religious communication, but also represents the cultural identity of the palace environment, which became the social basis for the birth of the two commentaries. In interpreting the concept of jihad in QS. al-Taubah [9]: 73, the Qur’an Jawen articulates jihad as sincerity in preaching and practicing religion, not physical resistance against colonialism. Meanwhile, Tafsir Qur’an Jawen Pandum lan Panduming Dumadi recontextualizes the Jewish and Christian conflict in QS. al-Baqarah [2]: 113 as a critique of the internal divisions of Muslims. This finding shows that interpretation functions as an arena for the production of meaning influenced by power relations, as well as a cultural da’wah strategy that connects the message of the Qur’an with the reality of Javanese society. This research contributes to the development of Nusantara interpretation studies by demonstrating the relationship among local culture, religious authority, and the process of meaning formation within the tradition of Qur’anic interpretation.